S43 Results from the STAR-COVID19 trial, a double-blind RCT of stabilised, synthetic sulforaphane in hospitalised patients with suspected COVID19. (11th November 2022) - Long, MB; Abo-Leyah, H; Giam, YH; Vadiveloo, T; Hull, RC; Keir, HR; Pembridge, T; Alferes de Lima, D; New, BJM; Inglis, S; Gilmour, A; Hughes, C; et al.
Abstract : Introduction and Objectives: The transcription factor, Nrf2, can directly promote beneficial anti-oxidant and anti-inflammatory responses. In the STAR-COVID19 trial, hospitalised patients with confirmed or suspected COVID19 were treated with stabilised, synthetic sulforaphane (S-SFN)—an Nrf2 inducer—to evaluate impact on clinical status and systemic inflammation. Methods: Double-blind, randomised, placebo-controlled trial of S-SFN (300 mg S-SFN or placebo once daily for 14 days; allocation ratio 1:1; EudraCT 2020–003486-19) in Dundee, UK. Inclusion criteria were age ≥18 years, suspected or confirmed COVID19 or pneumonia and CURB65 score ≥1. The primary outcome was the 7-point WHO Clinical Status scale at day 15. Secondary outcomes included time to clinical improvement, length of hospital stay, and mortality. Blood samples were taken on days 1, 8 and 15 for exploratory analyses. To assess Nrf2 activity and inflammation, 45 serum cytokines were measured using the Olink Target48 panel and mRNA sequencing of peripheral blood leukocytes performed. Further, as key immune cells in COVID19 responses, select neutrophil functions such as migration, phagocytosis and extracellular trap formation were evaluated. Results: 133 participants (77.4% PCR-confirmed SARS-CoV-2 infection) were randomized from Nov 2020 to May 2021. 68 received placebo (61.8% male; age 63.6±13.8) and 65 received S-SFN (53.8% male; age 61.6±12.7). S-SFN treatment did not improve clinical status at day 15 (Intention-to-treat population; adjusted OR 0.87, 95%CI 0.41–1.83, p=0.712) and the trial was terminated due to futility. Time to clinical improvement (adjusted HR 1.02(0.70–1.49)), length of hospital stay (aHR 0.84(0.56–1.26)), or 29-day mortality (aHR 1.45(0.67–3.16)) were not improved with S-SFN treatment. 230 samples in total were utilised for serum cytokine measurement; Nrf2 targets implicated in cytokine storm, including IL6, IL1β and TNFα, were not significantly changed by S-SFN treatment. Interestingly, serum TGFα was significantly increased at day 15 in those receiving S-SFN compared with placebo (p=0.004; linear mixed effects model). S-SFN treatment did not significantly affect neutrophil functions investigated. Conclusion: S-SFN treatment did not improve clinical status at day 15 or modulate key inflammatory cytokines—however, changes in other factors were indicated. Further analyses, including transcriptomics, to delineate drug activity are currently ongoing.